Feasibility of full and rapid neuromuscular blockade recovery with sugammadex in myasthenia gravis patients undergoing surgery - a series of 117 cases - Vymazal, Tomas; Krecmerova, Martina; Bicek, Vladimír; Lischke, Robert (Therapeutics and clinical risk management, 2015)
PURPOSE: Myasthenia gravis (MG) is an autoimmune disease interfering with neuromuscular transmission. Patients are at risk of postoperative residual curarization (PORC) if nondepolarizing muscle relaxants are used. Clinically inapparent insufficient muscle strength may result in hypoventilation and postoperative bronchopneumonia. We describe a cohort of 117 cases in which sugammadex was used in MG patients undergoing surgery with muscle relaxation with rocuronium. METHODS AND PATIENTS: We anesthetized 117 patients with MG using rocuronium and sugammadex as neuromuscular blockade reversal agent. One hundred five patients underwent surgical thymectomy and 12 underwent cholecystectomy (five laparotomic and seven laparoscopic). We measured time from sugammadex administration to recovery and to extubation, using the TOF-Watch(®) (series of four consecutive electrical impulses [the train-of-four] >0.9). We tracked peripheral capillary oxygen saturation (SpO2) <95%, elevation of partial pressure of carbon dioxide (pCO2) >10% above baseline, number of reintubations within the first 48 hours, and number of pneumonias within 120 hours, postoperatively. Results were processed as average, minimum, and maximum values. RESULTS: The period needed to reach train-of-four of 0.9 following sugammadex administration was on average 117 seconds (minimum of 105 seconds/maximum of 127 seconds) and differed within deviation <10%. The time to extubation following sugammadex administration was on average 276 seconds (minimum of 251 seconds/maximum of 305 seconds) and differed minimally among patients as well. We observed no SpO2 <95%, no pCO2 elevation >10% above a baseline, no emergent reintubation within the first 48 hours, and no pneumonia diagnosed on clinical basis within 120 hours, postoperatively in all 117 patients. CONCLUSION: In this cohort of MG patients undergoing surgery using rocuronium and sugammadex, we did not observe any signs of postoperative residual curarization and respiratory depression. The neuromuscular blockade recovery was reliable, predictable, and rapid.
Keywords: sugammadex; neuromuscular blockade recovery; myasthenia gravis; general anesthesia